Selective Constraint on the Upstream Open Reading Frames That Overlap with Coding Sequences in Animals - Hsu, Ming-Kung; Chen, Feng-Chi (PLOS ONE, 2012)
Upstream open reading frames (uORFs) are translational regulatory elements located in 5′ untranslated regions. They can significantly repress the translation of the downstream coding sequences (CDS), and participate in the spatio-temporal regulations of protein translation. Notwithstanding this biological significance, the selective constraint on uORFs remains underexplored. Particularly, the uORFs that partially overlap with CDS with a different reading frame (overlapping uORFs, or “VuORFs”) may lead to strong translational inhibition or N-terminal truncation of the peptides encoded by the affected CDS. By analyzing VuORF-containing transcripts (designated as “VuORF transcripts”) in human, mouse, and fruit fly, we demonstrate that VuORFs are in general slightly deleterious - the proportion of genes that encode at least one VuORF transcript is significantly smaller than expected in all of the three examined species. In addition, this proportion is significantly smaller in fruit fly than in mammals, indicating a higher efficiency of removing VuORFs in the former species because of its larger effective population size. Furthermore, the deleterious effect of a VuORF depends on the sequence context of its start codon (VuAUG). VuORFs with an optimal VuAUG context are more strongly disfavored than those with a suboptimal context in all of the three examined species. And the propensity to remove optimal-context VuAUGs is stronger in fruit fly than in mammals. Intriguingly, however, the currently observable optimal-context VuAUGs (but not suboptimal-context VuAUGs) are more conserved than expected. These observations suggest that the regulatory functions of VuORFs may have been gained fortuitously in organisms with a small effective population size because the slightly deleterious effect of these elements can be better tolerated in these organisms, thus allowing opportunities for the development of novel biological functions. Nevertheless, once the functions of VuORFs were established, they became subject to negative selection.